Why Ethno Science is Important for Science Learning in South Papua ? - Hafsemi Rapsanjani; Rizki Adri Yohanes; Fredy; Dewi Pui Rahayu (Nusantara Journal of Multidisciplinary Science, 2024)
This research is a qualitative study with an emphasis on ethnography. It aims to show why ethnoscience is so important in science learning in South Papua. This research was conducted in Malind villages, primary schools in Merauke Regency. The research method used was descriptive survey with data collection tools through observation, interviews, participation, documentation, and cultural literature of the Malind Tribe. In this research, the researcher acts as a human instrument (main instrument) who observes and explores directly the objects observed. The results showed: firstly, ethno-science in the indigenous culture of the Malind tribe can be found in cultural activities and daily life such as hunting, fishing, musical instruments, traditional ceremonies, food processing, determining tides, and eating betel nut. Secondly, the lack of teacher innovation in teaching science at school, science learning content has not contextually linked science learning with the cultural activities of the Malind tribe. The importance of ethnoscience in science learning is that the traditional science of the Malind tribe in Merauke can be integrated into science learning to instil the value of nationalism through strengthening local wisdom. By converting traditional science into scientific science, students can experience a contextualised and meaningful learning experience. Cultural elements become learning resources that are developed into tools and curriculum to improve students' science literacy, learning outcomes, and critical thinking skills.